Water–Food Nexus through the Lens of Virtual Water Flows: The Case of India - Suparana Katyaini (Water, 2021)
For a water-secure present and future, there is a need for a transition from water scarcity towards water security. This transition necessitates a look at the complex relationships, and interdependencies, between water and other resources, and the institutions governing them. Nexus approach encompasses these interdependencies. This paper focused on the water–food nexus through the lens of the virtual water (VW) flows concept with the aim to explore the role of the VW flows concept in governing the transition towards water security in a water-scarce economy like India. The key findings of the paper suggests that the highest VW outflows are from highly water-scarce states of India, such as Punjab and Andhra Pradesh, and the moderate to highly water-scarce state West Bengal from 1996–2014. Major VW outflows from these states are to other highly water-scarce states, resulting in the concentration of water scarcity. The main priorities for the governance of the water–food nexus in these states emerge from policies and action plans. These priorities are groundwater overexploitation, water and soil pollution, and uncertainty in rainfall and are linked to agricultural intensification. The water footprint-based VW flow analysis has important insights for sustainable intensification of agriculture, and rectification of the unsustainable VW flow patterns. The study concludes that the VW flows concept embodies the water–food nexus and is particularly relevant for the sustainable future of developing and emerging economies, such as India, grappling with water scarcity and challenges of fragmented environmental governance systems.